Inhibition of Stearoyl-CoA Desaturase Induces the Unfolded Protein Response in Pancreatic Tumors and Suppresses Their Growth. Issue 2 (February 2021) - Skrypek, Kaitlin; Balog, Steven; Eriguchi, Yoshihiro; Asahina, Kinji
Abstract : Objective: Pancreatic ductal adenocarcinoma is the fourth-leading cause of cancer death in the United States, and there is an urgent need for effective therapies. Stearoyl-CoA desaturase (SCD) is an enzyme localized in the endoplasmic reticulum and generates monounsaturated fatty acid from saturated fatty acid. In this study, we examined the role of SCD in pancreatic cancer. Methods: We isolated epithelial cell adhesion molecule-positive pancreatic tumors from the Pdx1 Cre ;LSL- Kras G12D mouse and formed organoids in Matrigel. Using a SCD inhibitor, A939572, we tested its effects on growth and cell death in tumor organoids, tumors developed in the Pdx1 Cre ;LSL- Kras G12D mouse, and a human pancreatic ductal adenocarcinoma cell line, PANC-1. Results: A939572 treatment rapidly induced degeneration of mouse tumor organoids and activated the unfolded protein response (UPR). Cotreatment of oleic acid, but not stearic acid, reduced the UPR in the organoids and rescued the inhibitory effect of the SCD inhibitor on their growth. Administration of A939572 to Pdx1 Cre ;LSL- Kras G12D mice caused cell death in early pancreatic tumors, but not in acini or islets. The SCD inhibitor induced the UPR in PANC-1 and suppressed their growth but did not induce cell death. Conclusions: The inhibition of the SCD enzyme causes an UPR and cell death in early pancreatic tumors.